Comparison of pregnancy outcome after fresh embryo transfer between GnRH antagonist and GnRH agonist regimens in patients with thin endometrium - Zhao, Depeng; Xie, Rui; Li, Xuemei (Frontiers in Medicine, 2023)
Objective: To compare the pregnancy outcome after fresh embryo transfer between GnRH antagonist and GnRH agonist protocols in patients with thin endometrium. Methods: This retrospective study included all fresh embryo transfers following GnRH agonist or GnRH antagonist protocols in patients with thin endometrium from 2018 to 2022. The thin endometrium was defined as an endometrial thickness of 7.5 mm or less on triggering day. Multivariant regression analysis was performed to evaluate the association of GnRH agonist or GnRH antagonist protocols with live birth after fresh embryo transfer in patients with thin endometrium. Results: A total of 69 and 192 cases were respectively included in the GnRH antagonist or GnRH agonist group. The stimulation duration was significantly longer by the GnRH agonist protocol than the GnRH antagonist protocol (11.2±2.1 vs 9.1±1.9 days, P=0.002). The clinical pregnancy rate and live birth rate were significantly lower in the GnRH antagonist group than in the GnRH agonist group (26.1% vs 47.9%, P=0.027; 17.4% vs 40.1%, P=0.01, respectively). Multivariable regression analysis showed that GnRH agonist protocol was associated with higher live birth rate after fresh embryo transfer compared with GnRH agonist protocol (adjusted OR: 2.5, 95%CI: 1.23-5.15). No significant difference in miscarriage rate and neonatal outcome was present between the two protocols. Conclusion: Our findings suggest that GnRH agonist protocol results in higher rate of live birth after fresh embryo transfer compared to GnRH antagonist protocol in patients with thin endometrium.